Implikasi Program bantuan Pemerintah Terhadap Peningkatan Kompetensi Guru Ngaji Di Kabupaten Jember: The Implications of Government Assistance Programs on the Improvement of Qur’an Teacher Competence in Jember Regency - Aris Maya; Moch. Chotib; Ahmad Royani (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
The number of Quranic teachers in Jember Regency surged dramatically from approximately 8,000 to 25,271 following the implementation of a government assistance program, raising critical questions about whether this quantitative increase aligns with improved teacher competence. This study aims to analyze the implications of government social assistance on the professional competence of Quranic teachers. Using a qualitative approach with a case study design, data were collected through interviews, documentation, and observation. The findings reveal that the assistance, funded by the Jember Regency APBD social expenditure budget, was distributed to 25,271 Quranic teachers across 31 sub-districts and 247 villages, with each teacher receiving IDR 400,000. The program significantly enhanced teacher competence by improving welfare, enabling them to focus on their instructional roles, create engaging learning environments, and achieve effective Al-Qur’an teaching outcomes. The study concludes that adequate welfare positively correlates with teacher professionalism and recommends increasing the assistance amount and establishing a regional regulation for Quranic teacher incentives. Jumlah guru ngaji di Kabupaten Jember meningkat drastis dari sekitar 8.000 menjadi 25.271 setelah adanya program bantuan pemerintah, sehingga memunculkan pertanyaan krusial apakah peningkatan kuantitas ini sejalan dengan kompetensi mereka. Penelitian ini bertujuan menganalisis implikasi bantuan sosial terhadap peningkatan kompetensi profesional guru ngaji. Dengan pendekatan kualitatif dan desain studi kasus, data dikumpulkan melalui wawancara, dokumentasi, dan observasi. Temuan penelitian menunjukkan bahwa bantuan yang bersumber dari pos belanja sosial APBD Jember tersebut disalurkan kepada 25.271 guru ngaji di 31 kecamatan dan 247 desa, masing-masing menerima Rp400.000. Program ini berimplikasi penting terhadap peningkatan kompetensi karena kesejahteraan yang memadai mendorong guru ngaji fokus melaksanakan tugas, peran, dan fungsinya secara maksimal, sehingga proses pembelajaran Al-Qur’an berlangsung optimal dan menyenangkan. Kesimpulannya, kesejahteraan yang layak berkorelasi positif dengan profesionalisme guru. Rekomendasi penelitian adalah peningkatan nominal bantuan dan pembentukan peraturan daerah tentang insentif guru ngaji.